The Prevalence and Pattern of Traditional Herbal Medicine Use during Pregnancy, Labour, and Postpartum: Implications for Prevention of Mother to Child Transmission of HIV in South Africa - Sphiwe Madiba; Irene Ledwaba (Tehran University of Medical Sciences, 2021)
The use of traditional herbal medicines (THM) is widespread among pregnant women in many African societies. Cultural beliefs and social norms largely influence the use of THM. However, its use during pregnancy is not freely discussed during antenatal care and the extent of its use remains unknown. The aim of the study was to determine the prevalence and pattern of THM use during pregnancy, labour, and post-delivery. The study was a quantitative cross-sectional design using a researcher administered questionnaire. Postnatal women enrolled in the prevention of mother to child transmission of HIV (PMTCT) were recruited from healthcare facilities in a rural South African sub-district. Summary and inferential statistics were computed using STATA 14.0 statistical package. The sample consisted of 399 women with mean age of 28 years. A high proportion (158/42.5) were receiving antiretroviral treatment. The prevalence of THM use was 23% and 76/87.4% took THM in the second trimester of pregnancy, 50/57.5% used THM throughout pregnancy, and 27/60% ingested THM when labour started. The majority (50/58.1%) used one type of THM and 35/41.5% used up to four types. The prevalence of THM use on babies was 44%, 82/54.2% were introduced to THM before three months, and 22/14.2% within their first week of life. A third 52/32.3% of babies received more than one concoction of herbal medicines. The women took THM to protect mother and baby from evil spirits as well as to increase labour pains and shorten the duration of labour. The use of THM on the baby was despite the women being enrolled in the PMTCT program which advocates exclusive breastfeeding (EBF) in the first six months. Mixed feeding practices including the use of THM on the baby before the end of the period of EBF have a negative impact on the elimination of vertical transmission of HIV.